Mathematical modeling of transients in the mine electric network using matrix-topological method - Сивокобиленко, Віталій Федорович; Василець, Святослав Володимирович (Technology audit and production reserves, 2015)
It is developed a mathematical model of the mine electric network, which allows us to analyze the transient and steady-state processes in normal and emergency modes. The model is a matrix differential equation in the form of Cauchy, compiled using matrix-topological method, which is different, taking into account the mutual influence of network components. The relevance of the analysis of transients in the mine electric network due to low precision of existing methods and the need to improve the technical and economic performance of the mining equipment. This mathematical model is applied in the form of a computer program with a graphical interface, which automatically calculates the matrix coefficients of the differential equation of condition of mine electric network and integrates its by hard-sustainable Gear-Nordsieck method. Using the proposed computer program by design organizations will increase the efficiency of the design process and increase the accuracy of determining the settings of protective devices.